Designing a Model for Developing Strategic Thinking of Islamic Azad University Administrators - Rasouldasht, Younes; Beikzad, Jafar; Beagzadeh, Yousef; Nejad Haji Ali Irani, Farhad (Iranian Journal of Educational Sociology, 2022)
Purpose: The current research, which is of the grounded theory type, was carried out with the aim of designing a model for developing strategic thinking of Islamic Azad University administrators. Methodology: The statistical population of this research is academic experts who have experience and education related to research in Azad University. The snowball method was used for sampling and the number of samples increased until reaching theoretical saturation, and finally 25 people were selected as the sample. To analyze the data obtained from the (semi-structured) interviews, the coding method was used in the grounded theory. In such a way that the data obtained from the interviews have been used in the three-step process of open, central and selective coding in accordance with the grounded theory process. Findings: The findings of the research indicated that the causal conditions include 1. Individual factors, 2. Organizational factors, 3. Discourse creation. The central phenomenon includes the development of managers' strategic thinking, which includes 1. Individual dimension, 2. Intuitive dimension, 3. Systemic view. Contextual factors include 1. Cultural platform 2. Learning context 3. Psychological factors 4. Organizational independence. And intervention factors include environmental factors in two dimensions a) within the organization and b) out of the organization. The strategies include talent management in two dimensions a) (talent acquisition) b) recruitment and retention. Conclusion: As a result, human resource empowerment activities, job satisfaction and performance of employees increases because the role of employees in realizing the organization's goals increases as a result of their empowerment.